Assessment of diabetic patient waiting & consultation time in a primary healthcare clinic - Shalihin, Mohd Shaiful Ehsan; Osman, Iskandar Firzada; Din, Muhammad Hapizie (2018)
 Patient satisfaction is of increasing importance and recognized as an important indicator for quality of care. It is influenced by the patients, physicians and practice's characteristics. 1,2  The literature on diabetes has increasingly focused on the quality of care and its measurement. Long waiting time is a common issue brought up by diabetic patients mainly in the early morning of a busy health clinic. 1,2  The relationship between the quality of diabetes care and patient satisfaction including appropriate clinic time spent by patient is poorly understood and it requires further elaboration. 2  Therefore, this audit aims to assess diabetic patients’ waiting time and consultation time in a public clinic in order to formulate strategies for improvement.